The Size Distribution of Businesses. Part I: A Benchmark Case - John Sutton (The Research Institute of Industrial Economics (IUI), 1996)
This paper examines the evolution of a skew distribution of firm sizes from the viewpoint of the 'Bounds' approach to market structure. It confines attention to the role played by non-strategic factors (statistical independence, and cost side effects). A model is proposed, which leads to a prediction regarding the least skew size distribution which is likely to be observed. This distribution provides a benchmark relative to which the impact of strategic effects on the form of the size distribution may be assessed.
Keywords: D21; L11; L15; 330; DISTRIBUTION; ENTERPRISES